Jerusalem from the Ottomans to the British - Mazza, Roberto (Library of Middle East history, 2014)
Roberto Mazza discusses the period of transition from Ottoman rule to the British administration, focusing on the socio-political changes from the nineteenth century to the twentieth, the impact of the First World War and the ongoing development of Jerusalem into the vibrant city it has become